Investigation of Content Parameters in Wet-Fractionated Fibre from Various Plants for Potential Use in Human Nutrition - Gábor Csatári; Bence József Eged; Csaba Fehér; Miklós Gábor Fári; Szilvia Kovács (Foods, 2022)
Green biorefining uses fresh lignocellulosic biomass to produce green juice and pressed fibre fractions by wet fractionation. The latter is a byproduct, accounting for 25–32% of the starting material. In this study, the composition (glucan, xylan, arabinan, lignin, total phenol, flavonoid and protein) of pressed fibres obtained from four alfalfa, four soy and one broccoli varieties were determined at different harvest times. Statistical analyses were performed to determine the effects of harvest time and variety on the measured parameters. In most of the cases, there were interactions between the effects of harvest time and variety. Among alfalfa varieties, OLI1 had the highest carbohydrate (52.09 w/w%) and DIM3 had the lowest lignin (13.02 w/w%) content. In the case of soy, the ADV2 variety had the highest carbohydrate (53.47 w/w%) and PK1 had the lowest lignin (11.14 w/w%) content. Broccoli contained low amounts of carbohydrates (44.94 w/w%) and lignin (10.16 w/w%). The phenolic and flavonoid contents were similar for each species, but the protein content was the highest in alfalfa fibre. Based on these data, the most promising species, varieties and harvesting time can be selected in terms of a certain component that could be essential to produce functional foods with enhanced nutritional value.